Relative Importance of Risks in Hydropower Projects and Project Finance in Nepal - Nepal, Achyut; Khanal, Vishnu; Maelah, Ruhanita (Journal of Advanced Academic Research, 2021)
Hydropower is the sole internal source of electricity in Nepal. Since the government policy of private participation in hydropower sector launched, Independent Power Producers (IPPs) have gained significant presence under Public-Private Partnership (PPP) model of infrastructure development.  Risk management is crucial in PPP projects as mishandling of any risk threatens sustainability and may result in project failure. This study analyses four major risks including Hydropower Sector Specific Risks, Project Finance Specific Risks, Hydropower Project Financing Risks and Country Specific Political and Legal Risks. Self-administrative survey utilizing questionnaire was conducted among the IPPs and domestic Banking and Financial Institutions (BFIs). Relative Importance Indices have been used to determine the importance of each risk item. Exchange rate changes, currency mismatch between local revenue and foreign loan, cost and time overrun, inflation, political turmoil and highly volatile political environment are few of the most critical risks found. For Project Finance proper allocation of risks among the stakeholders is crucial to make the projects bankable. Findings from this study indicate no risk should be neglected and relative importance of risks is critical in allocating risks among stakeholders. This study highlights assessment and the use of RII in the process of allocation and management of risks in infrastructure projects in general and hydropower in particular.